Cardiac intensive care unit: where we are in 2023 - Bouchlarhem, Amine; Bazid, Zakaria; Ismaili, Nabila; El Ouafi, Noha (Frontiers in Cardiovascular Medicine, 2023)
Cardiac intensive care has been a constantly evolving area of research and innovation since the beginning of the 21st century. The story began in 1961 with Desmond julian's pioneering creation of a coronary intensive care unit to improve the prognosis of patients with myocardial infarction, considered the major cause of death in the world. These units have continued to progress over time, with the introduction of new therapeutic means such as fibrinolysis, invasive hemodynamic monitoring using the Swan-Ganz catheter, and mechanical circulatory assistance, with significant advances in percutaneous interventional coronary and structural procedures.Since acute cardiovascular disease is not limited to the management of acute coronary syndromes, it also includes other emergencies such as severe arrhythmias, acute heart failure, cardiogenic shock, high-risk pulmonary embolism, severe conduction disorders and postimplantation monitoring of percutaneous valves, as well as other non-cardiac emergencies, such as septic shock, severe respiratory failure, severe renal failure and the management of cardiac arrest after resuscitation, for all these reasons, the conversion of coronary intensive care units into cardiac intensive care units represented an important priority.Today, the CICU concept is widely adopted by most healthcare systems, whatever the country's level of development. The main aim of these units remains to improve the overall morbidity and mortality of acute cardiovascular diseases, but also to manage other noncardiac disorders, such as sepsis and respiratory failure. This diversity of tasks and responsibilities has enabled us to classify these CICU s according to several levels, depending on a variety of parameters, principally the level of care delivered, the staff assigned, the equipment and technologies available, the type of research projects carried out, and the type of connections and networking developed. The European society of cardiology (ESC) have detailed this organization in guidelines published , with the aim of harmonizing the structure, organization and care offered by the various CICU s. In this state-of-the-art report, we review the history of the CICUs from the creation of the very first unit in 1968 to the discussion of their current perspectives, with the main objective of knowing what the CICUs will have become by 2023.